Mucosal‐associated invariant T (MAIT) cells are depleted and prone to apoptosis in cardiometabolic disorders. Issue 9 (27th April 2018) - Touch, Sothea; Assmann, Karen E.; Aron-Wisnewsky, Judith; Marquet, Florian; Rouault, Christine; Fradet, Magali; Mosbah, Helena; Consortium, MetaCardis; Isnard, Richard; Helft, Gerard; Lehuen, Agnes; Poitou, Christine; et al.
ABSTRACT: The disruption of systemic immune homeostasis is a key mediator in the progression of cardiometabolic diseases (CMDs). We aimed to extend knowledge regarding the clinical relevance of CMD‐associated variation of circulating mucosal‐associated invariant T (MAIT) cell abundance and to explore underlying cellular mechanisms. We analyzed cross‐sectional data from 439 participants of the Metagenomics in Cardiometabolic Diseases (MetaCardis) study, stratified into 6 groups: healthy control subjects and patients with metabolic syndrome (MS), obesity, type 2 diabetes mellitus (T2DM), and coronary artery disease (CAD) without, or with congestive heart failure (CAD‐CHF). Blood MAIT cell frequency was significantly decreased in all CMD groups, including early (MS) and later (CAD and CAD‐CHF) stages of disease progression. Reduced MAIT cell abundance was associated with increased glycosylated hemoglobin, inflammation markers, and deterioration of cardiac function. Glucose dose dependently promoted MAIT cell apoptosis in vitro, independently of anti‐CD3 and cytokine‐mediated activation. This outcome suggests the prominence of metabolic over an antigenic or cytokine‐rich environment to promote MAIT cell reduction in patients with CMD. In summary, all stages of CMDs are characterized by reduced circulating MAIT cells. Chronically elevated blood glucose levels could contribute to this decline. These data extend the pathologic relevance of MAIT cell loss and suggest that MAIT cell abundance may serve as an indicator of cardiometabolic health.—Touch, S., Assmann, K. E., Aron‐Wisnewsky, J., Marquet, F., Rouault, C., Fradet, M., Mosbah, H., MetaCardis Consortium, Isnard, R., Helft, G., Lehuen, A., Poitou, C., Clément, K., André, S. Mucosal‐associated invariant T (MAIT) cells are depleted and prone to apoptosis in cardiometabolic disorders. FASEB J. 32, 5078–5089 (2018). www.fasebj.org